Integrated Analysis of Transcriptome Data Revealed AURKA and KIF20A as Critical Genes in Medulloblastoma Progression - Liang, Bo; Zhou, Yan; Jiao, Jiji; Xu, Lixia; Yan, Yan; Wu, Qiaoli; Tong, Xiaoguang; Yan, Hua (Frontiers in Oncology, 2022)
Medulloblastoma is the neuroepithelial tumor with the highest degree of malignancy in the central nervous system, accounting for about 8% to 10% of children's brain tumors. It has a high degree of malignancy and is easily transmitted through cerebrospinal fluid, with a relatively poor prognosis. Although medulloblastoma has been widely studied and treated, its molecular mechanism remains unclear. To identify the key genes in the development and progression of medulloblastoma, we analyzed three microarray datasets from Gene Expression Omnibus (GEO). Differentially expressed genes (DEGs) were identified and analyzed by Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG). Protein interaction network (PPI) was constructed, and the hub genes were identified by different evaluation methods in cytoHubba, and the target genes were screened out by survival analysis。Finally, human medulloblastoma samples were used to verify the expression of target genes. In conclusion，This study found that aurora kinase A (AURKA) and kinesin family member 20A (KIF20) may be involved in the occurrence and development of MED, and are closely related to prognosis, and may become a potential therapeutic target and prognostic marker of MED.